Clinical dose finding study on NM441 in complicated urinary tract infections - Ban, Yoshihito; Kamidono, Sadao; Arakawa, Soichi; Ohmori, Hiroyuki; Hirose, Takaoki; Kawada, Yukimichi; Kumazawa, Joichi; Tanaka, Yutaka; Nagayama, Ariaki; Kumon, Hiromi; Matsumoto, Tetsuro; Kumamoto, Yoshiaki (Japanese Journal of Chemotherapy, 1996)
In order to investigate the clinical optimal dose of NM441, a new quinolone antimicrobial agent, for complicated urinary tract infections, a dose finding study was performed, using ofloxacin (OFLX) as a control drug. Subjects were patients with complicated urinary tract infections accompanied by underlying disease in urinary tract, who were more than 20 and less than 80 years old, and no catheter indwelt cases. However, the patients who were less than 1 month after prostatectomy were excluded, and patient's sex and inpatient or out-patient were ignored. NM441 100mg (L group), 200mg (H group) twice a day, or OFLX 200mg (C group) three times a day was orally administered for consecutive 7 days. A total number of patients was 119, and 32 cases in the L group, 30 in the H group and 31 in the C group, excluded the cases of disqualification 17, withdrawal 4, dropping-out (failure of follow-up) 1 and treatment violation or noncompliance 4, were evaluated according to the criteria proposed by the Japanese UTI Committee. In the overall clinical efficacy, the efficacy rates were 75.0% in the L group, 73.3% in the H group and 90.3% in the C group, respectively, showing no significant difference among L group versus H group and 3 groups. The efficacy rates after adjustment for unequal distributions of study factors were 74.0% in the L group, 80.0% in the H group and 87.0% in the C group, respectively. In the bacteriological response, the eradication rates in the L group, H group and C group against gram-positive cocci were 71.4%, 77.3% and 70.0%, those against gram-negative rods were 87.5%, 90.5% and 100%, and those against a total of bacteria were 81.6%, 83.7% and 92.1%, respectively, showing no significant difference among L group versus H group and 3 groups. As for adverse reactions, 2 cases (5.3%) of the digestive symptoms were observed in the H group, and each 2 cases (10.3%) of the allergy symptoms and the digestive symptoms were observed in the C group. All of them were mild or moderate and disappeared without the particular treatment. The incidences of abnormal changes in laboratory findings were 8.1% in the L group, 14.7% in the H group and 6.1% in the C group, respectively. Although no significant differences were obtained between the L group and the H group in any results, the overall clinical efficacy rate after adjustment and the bacteriological response in the H group were higher than those in the L group. From the above results, the clinical optimal dose of NM441 for complicated urinary tract infections was considerd to be 200mg twice a day.